Implementasi Metode Forward Chaining dalam Sistem Pakar Pemilihan Pendidikan Berdasarkan Minat dan Kemampuan Siswa - Haerudin; Iqbaludin; Faisal Irsyad Noer; Perani Rosyani (CV. Multi Kreasi Media, 2023)
In order to select students to attend education according to their interests and talents, this research is a systematic literature review that aims to explore research related to the implementation of the forward chaining method in expert systems. The process of conducting a literature review involves conducting an extensive and focused search of pertinent scientific databases. We list and evaluate previous research in this area in this review. According to the conclusions of the review, the forward chaining technique has been widely used in the development of expert systems for various purposes, including educational selection. Using this technique, expert systems can quickly generate sensible educational recommendations based on students'interests and skills. The benefits and drawbacks of the forward chaining approach, as well as the methods and approaches used to create an expert system knowledge base, have also been emphasized in previous studies. To further improve the quality of educational recommendations, many studies have tried to combine the forward chaining method with additional technologies such as data mining and artificial intelligence. This literature review offers a thorough analysis of the use of the forward chaining method in educational selection expert systems and offers recommendations for future studies that will help create more sophisticated and useful expert systems in this field.